Numerical and experimental evaluation of the thermally stratified atmospheric boundary layer in wind tunnels - Teixeira,Renan de Souza (2021)
Abstract The atmospheric boundary layer (ABL) flow occurs due to the interaction between the Earth’s surface and atmosphere, and it usually happens under thermal stratification. Therefore, in order to emulate this phenomenon, atmospheric wind tunnels need appropriate devices, such as spires and cubical roughness elements, at the entrance of the wind tunnel to create atmospheric characteristics for the analysis. In the current study, numerical and experimental investigations of the thermally stratified boundary layer are performed. The experimental data are measured using Inmetro’s atmospheric wind tunnel. Two different spires set configurations and inlet velocities are considered. Moreover, the compressible Navier-Stokes equations using the k-epsilon turbulence model are computed by OpenFOAM opensource software. The simulated results and measured data presented a good overall agreement and showed that the proposed configuration provides the desired thermal and dynamic boundary layer necessary for the study of ABL.